The Influence of Capital and Online Marketing Strategies on MSME’s Development in Madiun City - Putri, Sedinadia; Yunita, Ratna (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: The Micro, Small, and Medium Enterprises Group (UMKM) in Madiun City is a facility for MSME actors with a business license. The goal of this MSME group is for their efforts to achieve maximum development results. However, the MSME group's business in Madiun City still needs to develop. This can be seen from the addition of capital and the use of technology in a marketing strategy that does not make the business being run develop. Based on these problems, this study aims to test and analyze whether capital and online marketing strategies positively affect the development of MSMEs in the MSME Group in Madiun City. Research Methods: The type of research used is quantitative research with a population of 300 and a sample of 75 respondents. This study uses the Probability Sampling technique of Simple Random Sampling and data collection methods using a questionnaire/questionnaire. Statistical data analysis technique using SPSS 16.0. This research uses validity, reliability, descriptive analysis, classical assumption test, t-test, f-test, multiple linear regression, and coefficient of determination. Result: The results of this study indicate that (1) capital has a positive and significant effect on the development of MSMEs in the MSME group in Madiun City, (2) online marketing strategies have a positive and significant effect on the development of MSMEs in the MSME group in Madiun City, (3) capital and strategies Online marketing simultaneously has a positive and significant effect on the development of MSMEs in the MSME group in Madiun City. Conclusion: Based on the results of hypothesis testing, it can be concluded that the capital variable and online marketing strategy simultaneously (together) have a positive and significant effect on the development of MSMEs in the MSME group in Madiun City.